2011
DOI: 10.1111/j.1432-2277.2011.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the aetiology and severity of liver disease on oral health and dental treatment prior to transplantation

Abstract: Summary Elimination of dental infection foci has been recommended before liver transplantation (LT) because lifelong immunosuppression may predispose to infection spread. Association between pre‐LT oral health and the aetiology and severity of chronic liver disease (CLD) was investigated retrospectively. A total of 212 adult patients (median age 51.1) who had received LT during 2000–2006 in Finland were included. Their oral health had been pre‐operatively examined. Patients were divided into seven different CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
1
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 26 publications
(29 reference statements)
8
47
1
17
Order By: Relevance
“…Most authors in the field of organ transplantation agree that teeth with obvious infections, and all non-restorable teeth, must be extracted prior to transplantation. Therefore, patients should be reminded of earlier dental treatment and the importance of good oral hygiene habits (30). Owing to oral complications, these patients require to visit a dentist before and after transplantation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Most authors in the field of organ transplantation agree that teeth with obvious infections, and all non-restorable teeth, must be extracted prior to transplantation. Therefore, patients should be reminded of earlier dental treatment and the importance of good oral hygiene habits (30). Owing to oral complications, these patients require to visit a dentist before and after transplantation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Managing of the oral health before organ transplantation includes several factors that must be considered (14,15,16,17,18,19): …”
Section: Managing the Oral Health Of Patients Prior To Liver Transplamentioning
confidence: 99%
“…Therefore oral and dental foci of infection should be managed radically if they are present, especially in medically compromised patients (14,15,16).…”
Section: Dental Focus (Odontogenic Focus Disturbance Field) Of Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…As concluded by the researchers, patients with periodontitis may have greater salivary dysbiosis. We have shown that, after careful oral examination, on average, one to two teeth needed extraction because of severe periodontitis in patients with alcoholic liver cirrhosis under evaluation for liver transplantation (LT) (2) ; this demonstrates high prevalence of periodontitis in advanced liver cirrhosis.…”
Section: To the Editormentioning
confidence: 99%